(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This research article has put forward an innovative analytical result of the 2D heat equation having a source term. The aforesaid non-homogenous PDE is solved through a new hybrid mechanism. whereas the technique supports the solution process, commencing with the parametric form of the 2D heat equation. Furthermore, this hybrid mechanism which consists of Natural transform (NT) and a series solution method of Adomian decomposition method (ADM) is applied properly. Next, the solution that is obtained for the unknown function is presented in series form. During the computational process, it was observed that the proposed mechanism is less time-consuming and efficient with accurate results. Which shows that the mechanism (proposed mechanism) makes a very useful contribution to the analytical solution of the 2D heat equation. The paper is properly supported with appropriate examples to verify the claim.